Hypersensitivity Reactions in Serious Adverse Events Reported for Paracetamol in the EudraVigilance Database, 2007-2018 - Iwona Popiołek; Katarzyna Piotrowicz-Wójcik; Grzegorz Porebski (MDPI AG, 2019)
Paracetamol is a popular and easily available drug which is used world-wide as analgesic, antipyretic agent. Hypersensitivity reactions to this drug involve a wide range of symptoms of various importance for patient management. The EudraVigilance (EV) database serves as a system for monitoring adverse events (AE) due to drug intake. We retrospectively recorded AE reports for “paracetamol” reported from 1 January 2007 to 1 October 2018 which fulfilled the category of “serious” in EV. For further analysis the retrieved AE reports were selected according to the keywords corresponding to hypersensitivity symptoms. We included in the study 4589 AE reports with 9489 particular AEs. 24.2% of all the AE reports concerned children. The most often reported symptoms were “angioedema,” “rash” and “urticaria” (each of them with a frequency of >10% in the AE reports). An important group of AEs were oedema reported as being located in the head, neck or respiratory tract. We recorded 58 AE reports with fatal outcomes, including 9 Stevens-Johnson syndrome/toxic epidermal necrolysis cases (SJS/TEN), 10 anaphylactic reactions, 21 cases of hepatic failure and a further 18 cases which occurred for other reasons. SJS/TEN, acute generalized exanthematous pustulosis and drug reaction with eosinophilia and systemic symptoms were reported 129, 42 and 25 times, respectively. Prodromes and symptoms of potentially life-threating SJS/TEN appeared in 286 of the AE reports. 380 AE reports pointed to a diagnosis of anaphylaxis. To improve patient safety, healthcare professionals, including pharmacists, can identify warning signs of severe hypersensitivity reactions to paracetamol.